HOLTEKAMP JAYAPURA BRIDGE CONSTRUCTION PROJECT: THE ANALYSIS OF RAW MATERIAL SUPPLIERS’ SELECTION - Karunia Ika Pertiwi; Eka Bambang Gusminto; Didik Pudjo Musmedi (BISMA: Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study is to determine the priority of raw material suppliers in Holtekamp Jayapura bridge construction project. Data collection techniques include an interview and a questionnaire conducted with 3 (three) expert respondents using a comparison scale of 1-9. A total of 4 (four) criteria have been examined in this research, namely price, quality, shipping speed, and product capacity. This study included 8 (eight) alternative suppliers. The method applied was the Analysis Hierarchy Process (AHP) using Expert Choice V.11 software. The results revealed that the price criteria ranked first, the quality criteria ranked second, the criteria for sending speed ranked third, and the weight and product capacity criteria ranked fourth. Accordingly, Agung M, Sultan, SKB, Youtefa, Bumi Infrastruktur, Bintang M, Simpama Dwi, and Rajawali rank highest among raw material suppliers in the order of 1-8. Thus, it is indicated that Agung M, Sultan, and SKB are the 3 (three) best suppliers that the company should choose.